A Study on the Development of Winter Sports Tourism in China - Chen, Hongbing (Technium Social Sciences Journal, 2022)
In the present study, two time periods were selected to obtain critical data, the first period is 2010-2019, and the second one is 2022. The literature related to winter sports tourism from 2010-2019 and 2022 was checked to review the history of winter sports tourism in China. Winter sports tourism development in China was obtained from 2010-2019 and 2022. The comparative analysis of a large amount of data found that the development of China's winter sports tourism industry is linear, and the overall development level is rising. Before 2015, China's ski resort infrastructure was poor, the number of people involved in winter sports tourism was low, and the demand for winter sports tourism in China had to be met abroad. After Beijing won the right to host the 2022 Winter Olympics and Winter Paralympics in 2015, China proposed to let 300 million people Participation in winter sports, and the country officially vigorously developed the winter sports industry. 2016-2022, China's winter sports tourism heavy asset projects close to 1 trillion, and the total investment reached 2.47 trillion yuan. China's winter sports characteristics in the town gradually increased, improving the construction of ski resort infrastructure, deep excavation of cultural connotations, and active propaganda. Whether the number of people involved in skiing, the category of people involved in skiing, or the level of participants in skiing has a greater changed than before.